2022
DOI: 10.1039/d1ma01095f
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation induced delayed green fluorescence from assembly of gold nanoclusters: an advanced probe for “background free” pyrophosphate recognition

Abstract: Aggregation induced emission (AIE), ever since its inception, has received remarkable attention of scientists pursuing research towards development of advanced optical materials. Thus, a plethora of light emitting materials have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…Gold nanoclusters (Au NCs) were prepared by introducing mercaptopropionic acid (MPA) into an aqueous solution of tetrachloroauric acid, following established protocols. 31 Consistent with our earlier findings, the synthesized Au NCs exhibited a faint luminescence (Fig. S1A, ESI †) and the UV-vis spectrum featured a broad absorbance from 200 nm to 400 nm (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Gold nanoclusters (Au NCs) were prepared by introducing mercaptopropionic acid (MPA) into an aqueous solution of tetrachloroauric acid, following established protocols. 31 Consistent with our earlier findings, the synthesized Au NCs exhibited a faint luminescence (Fig. S1A, ESI †) and the UV-vis spectrum featured a broad absorbance from 200 nm to 400 nm (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Unlike the nonradiative nature of the AuNCs, the addition of Zn resulted in the appearance of an intense emission peak with a maximum at 485 nm, ( Figure b), having a long radiative averaged lifetime of ∼12.1 ns (Figure b inset) with a calculated quantum yield of 7.4%. This calculated quantum yield value of Zn-AuNCs is well corroborated with previous reports . To further validate that the addition of Zn ions is the cause for the emergence of radiative processes, we followed the time-resolved fluorescence of the AuNCs while titrating them with Zn ions, showing a gradual increase in the radiative lifetime (Figure S3).…”
Section: Resultssupporting
confidence: 89%
“…This calculated quantum yield value of Zn-AuNCs is well corroborated with previous reports. 48 To further validate that the addition of Zn ions is the cause for the emergence of radiative processes, we followed the time-resolved fluorescence of the AuNCs while titrating them with Zn ions, showing a gradual increase in the radiative lifetime (Figure S3).…”
Section: Resultsmentioning
confidence: 98%
“…They revealed that long lifetime (1.9 μs) and high quantum yield (31%) of Au−Cu−NCs is the outcome of TADF, which originates from Cu doping-induced small ΔE ST and large spin− orbit coupling (SOC). Santanu et al 103 reported a fascinating discovery in which nonluminescent gold nanoclusters, when subjected to complexation reactions with zinc ions, demonstrated delayed fluorescence characterized with a high quantum yield of 6% and microsecond lifetime. These aggregated gold clusters exhibited delayed green fluorescence, which was subsequently employed for the "background-free" detection of pyrophosphate ions.…”
Section: Tailoring Ligands To Enhance Long-lived Emissionmentioning
confidence: 99%